2005
DOI: 10.1369/jhc.5c6659.2005
|View full text |Cite
|
Sign up to set email alerts
|

Resin Tissue Microarrays: a Universal Format for Immunohistochemistry

Abstract: S U M M A R YTissue microarray (TMA) technology allows the miniaturization and characterization of multiple tissue samples on a single slide and commonly uses formalin-fixed paraffin-embedded (FFPE) tissue or acetone-fixed frozen tissue. The former provides good morphology but can compromise antigenicity, whereas the latter provides compromised morphology with good antigenicity. Here, we report the development of TMAs in glycol methacrylate resin, which combine the advantages of both methods in one embedding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…This is not possible with the whole hair method (Camidge et al, 2005b) where the whole sample has to be used for each stain employed.The new methodology subsequently permits considerably greater flexibility in workload scheduling by avoiding the necessity for multiple sampling from each volunteer at each time point in the study. The great advantage of methyl methacrylate in immunohistochemistry over other commonly used resins is the ability to remove the resin by immersion in xylene (Britten et al, 1993;Howat et al, 2005), the consequence being that IHC methods developed on FFPE tissues may be transferred to MMA embedded tissues with little or no modification. This is advantageous to the investigator, saving time in method development and strengthening confidence in the assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not possible with the whole hair method (Camidge et al, 2005b) where the whole sample has to be used for each stain employed.The new methodology subsequently permits considerably greater flexibility in workload scheduling by avoiding the necessity for multiple sampling from each volunteer at each time point in the study. The great advantage of methyl methacrylate in immunohistochemistry over other commonly used resins is the ability to remove the resin by immersion in xylene (Britten et al, 1993;Howat et al, 2005), the consequence being that IHC methods developed on FFPE tissues may be transferred to MMA embedded tissues with little or no modification. This is advantageous to the investigator, saving time in method development and strengthening confidence in the assay.…”
Section: Discussionmentioning
confidence: 99%
“…The great advantage of methyl methacrylate in immunohistochemistry over other commonly used resins is the ability to remove the resin by immersion in xylene (Britten et al, 1993; Howat et al, 2005), the consequence being that IHC methods developed on FFPE tissues may be transferred to MMA embedded tissues with little or no modification. This is advantageous to the investigator, saving time in method development and strengthening confidence in the assay.…”
Section: Discussionmentioning
confidence: 99%
“…This involves heating of the block three or four times for 1-8 hr at 35C in an oven and then cooling on a cooling plate (or in a−4C freezer) for 15 min. Howat et al (2005) reported a resin TMA in which a glycol methacrylate resin array block was cut with a rotary microtome. Agarose was used as an intermediary recipient block to produce the resin array block through a long and complicated procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the resin tissue microarray technology (Howat et al 2005;Howat and Wilson 2010), the advantage of resin as an embedding medium that allows for very thin (down to 0.5 mm) sections with excellent tissue morphology (Britten et al 1993) has been combined with the improved antigenicity of acetone fixation for immunohistochemistry analysis. An important limitation of the resin technology is that punches cannot be cored from existing resin blocks, so that resin TMAs can only be build from nonembedded (fixed or frozen) tissues.…”
Section: Methods For Tma Constructionmentioning
confidence: 99%